Technical characteristics of elite junior men and women race walkers - Hanley, B.; Bissas, A.; Drake, A. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: Successful coaching in race walking requires a thorough understanding of the biomechanical principles underlying this unique form of gait. The purpose of this study was to analyze elite male and female junior race walkers and identify key kinematic variables. METHODS: Twenty junior men and 20 junior women were videoed as they competed over 10 km in the 8th European Cup Race Walking. Three-dimensional kinematic data were obtained using motion analysis software (SIMI, Munich). RESULTS: Step length and cadence were correlated with speed in both sexes, and greater step lengths were the kinematic reason for junior men`s faster walking speeds. While cadence did not differ between junior men and junior women, there was a difference in proportion of step time spent in contact. There were some differences between genders for upper body joint angles (e.g., elbow) but there were few differences within lower limb joint angles. CONCLUSION: Although some technical aspects (e.g., pelvic and shoulder girdle rotation) appeared undeveloped, it was noteworthy that most athletes achieved full knee extension at initial contact in accordance with the rules. However, in many athletes flight times were evident that might present problems during the transition to the higher standards of senior competition. There was a large range of ability among both sexes and coaches are advised to ensure that technical development continues during the transition to senior competition.